Analisis Kinerja Keuangan Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2021 - Nelly; Dimas Try Handoko; Lia Sari; Roy Saleh; Berry Angga (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
The purpose of this study is to determine the financial performance of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2018-2021. Analysis of the data used is quantitative analysis using financial ratios, namely liquidity ratios, solvability ratios and profitability ratios.The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 2021. The sample used in this study is a manufacturing company in the consumer goods industry sector which is included in the LQ45 category. The results showed that the best financial performance in terms of company liquidity was PT Indofood CBP Sukses Makmur Tbk and PT Gudang Garam Tbk. The best financial performance in terms of Debt to equity ratio is PT Indofood CBP Sukses Makmur Tbk, PT Indofood Sukses Makmur Tbk, PT Gudang Garam Tbk, PT Hanjaya Mandala Sampoerna Tbk and PT Kalbe Farma Tbk. While the best financial performance in generating profits in terms of profitability is PT Unilever Indonesia, Tbk